Impact of Microgrid Operation on the Performance of Overcurrent Relay Coordination and Assessment of Differential Relay Coordination. Issue 9 (19th October 2020) - Kar, Susmita; Samantaray, Subhransu Ranjan
Abstract: Penetration of distributed generations (DGs) enable microgrid to operate in different mode such as grid-connected and islanded mode with radial and mesh topology. The fault current magnitude and direction varies according to the operating conditions which imposes serious protection challenges and may lead to protection system failure and nonselective relay operation. Thus, the impact of operating conditions on the existing overcurrent relay coordination has been extensively studied in this paper. The overcurrent relay coordination is implemented using genetic algorithm (GA) considering different topology and operating modes of the microgrid. Extensive test results indicate that the existing overcurrent relay coordination may fail during some critical operating conditions and thus, a differential relay coordination scheme is proposed which provides improved performance for microgrid operating in different modes and different network topologies with both synchronous and inverter-based DGs.